Security sieve: a technique for enhancing the performance of secure sockets layer-based distributed systems. Issue 5 (2nd September 2016) - Lim, Norman; Majumdar, Shikharesh; Srivastava, Vineet
ABSTRACT: Providing secure communication in distributed systems often introduces a performance penalty due to the CPU-intensive operations used by security protocols such as the Secure Sockets Layer (SSL) protocol. This paper proposes a technique, called security sieve, which enhances the performance of SSL-based document transmission. Security sieve separates the sensitive components from the non-sensitive components, and transmits the separated components over a secure channel and a (faster) non-secure channel, respectively. At the receiving end, the separated components are re-assembled to reconstruct the original document. A significant performance improvement with security sieve is observed for a number of system and workload parameters.